MENUMBUHKAN KESADARAN AKAN KEBERSIHAN UNTUK HIDUP BERKELANJUTAN DI SD NEGERI BIRINGKALORO KABUPATEN GOWA - Suratmi Dahlan; Nurfadilah; Nurul Hidayah; Trye Sunarti H; Irwan Akib; Ernawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Low awareness and implementation of Clean and Healthy Living Behavior (CHLB) among elementary school students remain a challenge that affects students’ health and the comfort of the learning environment. Limited understanding of the importance of personal and environmental hygiene as part of sustainable living practices became the basis for conducting a Community Service Program (PKM) in the form of hygiene awareness socialization at SD Negeri Biringkaloro, Gowa Regency. This activity aimed to improve students’ understanding and awareness in applying clean and healthy living behaviors as a disease prevention effort and to foster environmentally caring character, as part of the implementation of the Tri Dharma of Higher Education, particularly community service. The program was implemented collaboratively by lecturers and students of the Master’s Program in Primary Education at Universitas Muhammadiyah Makassar in cooperation with school teachers through planning, implementation, and reporting stages, using socialization methods supported by interactive discussions and ice-breaking activities. The results indicated that students participated enthusiastically and actively engaged throughout the activity. Therefore, this socialization program was effective in increasing hygiene awarenessand supporting the creation of a healthy and sustainable school environment